Clinical and metabolic implications of obesity in prostate cancer: is testosterone a missing link?. (2nd October 2019) - Duarte, M. F.; Luis, C.; Baylina, P.; Faria, M. I.; Fernandes, R.; La Fuente, J. M.
Abstract: Objectives: To assess sex hormones in men with obesity and prostate cancer (PCa) and to study association between androgens and the pathogenesis biology of PCa in vitro . Subjects and methods: One hundred and eighty-one men older than 45 years selected from of a population attending to Urology departments screening for PCa, (78 participants without PCa and 103 patients with PCa). All participants were assessed for body mass index (BMI), age, Gleason score, and PSA. Endocrine profile was determined for LH, total testosterone (TT), 17β-estradiol (E2), prolactin and leptin. Biochemical profile (HbA1c, triacylglycerols and lipoproteins) was also determined. In vitro experiments were also performed, involving the study of 5α-dihydrotestosterone (DHT) and E2 in the presence of adipocyte-conditioned medium (aCM). Results: All variables were continuous and described a Gaussian distribution unless mentioned. To determine the relation of aggressiveness, variable were transformed into categories. Thus, PCa aggressiveness is associated with the increase of age and BMI ( p < .0001) but with is decreased with TT and E2 ( p < .05). Moreover, adipocyte-secreted molecules increase aggressiveness of PCa cells in vitro . Lastly, DTH but not E2 enables invasiveness in vitro . Conclusions: It was observed a coexistence of hormone axis profile alteration with sex hormones and BMI in PCa patients, in accordance with the new perspective of PCa pathogenesis.